Uji Efek Antibakteri Ekstrak Etanol Herba Seledri (Apium graveolens Linn.) Terhadap Escherichia coli dan Staphylococcus aureus dan Analisis KLT Bioautografi - Khildah Khaerati; Ihwan Ihwan (Biocelebes, 2011)
This research divided into two stage which are the inhibition growth capacity test using agar diffusion method with the incubator period 1 x 24 jam hours as the first stage and second stage testing the TLC-Bioautographic. Sample made with the concentration 0,5%, 1 %, 2% and 4% w/v. The capacity of growth inhibited showed on Staphylococcus aureus and than. The TLC-Bioautographic test to the chromatogram of fractionation result with Chloroform : Metanol (15 : 6) on Escherichia coli 1 active stains with Rf value 0,32, for Staphylococcus aureus resulted 2 active stains with Rf value in a row 0,88 and 0,32 Key words: Antibacteri, Apium graveolens, bioautographic.